Metal dimer sites in ZSM-5 zeolite for methane-to-methanol conversion from first-principles kinetic modelling: is the [Cu–O–Cu]2+ motif relevant for Ni, Co, Fe, Ag, and Au?. Issue 7 (28th February 2017) - Arvidsson, Adam A.; Zhdanov, Vladimir P.; Carlsson, Per-Anders; Grönbeck, Henrik; Hellman, Anders
Abstract : Reaction energy landscapes for the direct conversion of methane to methanol over ZSM-5 for Cu, Ni, Co and Fe dimer sites. Abstract : Direct methane-to-methanol conversion is a desired process whereby natural gas is transformed into an energy-rich liquid. It has been realised at ambient pressure and temperature in metal ion-exchanged zeolites, where especially copper-exchanged ZSM-5 has shown promising results. The nature of the active sites in these systems is, however, still under debate. The activity has been assigned to a [Cu–O–Cu] 2+ motif. One remaining question is whether this motif is general and also active in other metal-exchanged zeolites. Herein, we use first-principles micro-kinetic modelling to analyse the methane-to-methanol reaction on the [Cu–O–Cu] 2+ motif, for Cu and other metals. First, we identify the cluster model size needed to accurately describe the dimer motif. Starting from the [Cu–O–Cu] 2+ site, the metal ions are then systematically substituted with Ni, Co, Fe, Ag and Au. The results show that activation of Ag and Au dimer sites with oxygen is endothermic and therefore unlikely, whereas for Cu, Ni, Co and Fe, the activation is possible under realistic conditions. According to the kinetic simulations, however, the dimer motif is a plausible candidate for the active site for Cu only. For Ni, Co and Fe, close-to-infinite reaction times or unreasonably high temperatures are required for sufficient methane conversion. As Ni-, Co- and Fe-exchanged ZSM-5 are known to convert methane to methanol, these results indicate that the Cu-based dimer motif is not an appropriate model system for these metals.